Temporal effect of continuous use of biosolid and effluent treated in the soil sodicity and salinity - Alves, Dávilla Alessandra da Silva [UNESP] (2019)
The objective of this study was to evaluate the effect of continuous use of sewage sludge and treated domestic effluent on the potential risk of soil sodicity and salinity. The experimental design was completely randomized in split plots with ten treatments and five replications. The plots consisted of the use of two types of irrigation water (treated domestic effluent AR and supply water AB) and the subplots by the biosolid doses (0, 50, 100, 150 and 200%) in the years 2012 to 2017. The electrical conductivity (EC), pH, Ca, Mg, Na, RAS and PST of the soil were evaluated. It was concluded that the effect of mineral fertilization (0%-control) with AB was similar to the effluent use in soil EC for the same treatment. Doses from 127.4% and 113.2% of biosolid, respectively, with RA and AB decreased the exchangeable Na content of the soil. Results indicated low risk of sodicity and salinity after five years of use.